A Five Country Study of Gender and Sexuality Diversity and Schooling in Southern Africa. Issue 1 (2nd January 2019) - Francis, Dennis A.; Brown, Anthony; McAllister, John; Mosime, Sethunya T.; Thani, Glodean T. Q.; Reygan, Finn; Dlamini, Bethusile; Nogela, Lineo; Muller, Marguerite
ABSTRACT: The importance of quality education provision for all is a globally acknowledged principle for the creation of sustainable learning environments at primary and secondary levels. This article reports on a study that aimed to increase understanding of the context of how gender and sexuality diversity is responded to in schools in Southern Africa. In this regard, the researchers drew on a recent five country study focusing on what the literature says about gender and sexuality diversity and schooling in Botswana, Lesotho, Namibia, South Africa and Swaziland. Drawing on a review of reports and publications by relevant ministries, policy documents, published research, relevant statistical data, as well as the grey literature from civil society organisations, the findings indicated significant barriers to access for learners who embody non-normative gender or sexualities. The policies and schooling cultures in Botswana, Lesotho, Namibia, South Africa and Swaziland foreground discourses that marginalize, silence and invisibilise gender and sexual minorities. The researchers argue that if educational institutions in the region are to include all learners, there must be real engagement with the ongoing realities of heterosexist exclusion and marginalisation. The findings pointed to the need for teacher education to step up efforts to prepare teachers in the region to comfortably and professionally engage with and teach about issues of gender and sexuality diversity in the classroom.